Self-Reported Disability in Persons With HIV-Related Neuropathy Is Mediated by Pain Interference and Depression. Issue 12 (10th September 2020) - Kietrys, David M; Parrott, James Scott; Galantino, Mary Lou; Davis, Tracy; Levin, Todd; O'Brien, Kelly K
Abstract: Objective: The purpose of this study was to compare disability in people with HIV and peripheral neuropathy with those without neuropathy and explore how neuropathy and other relevant factors are associated with disability. Methods: In this cross-sectional study, participants completed the Brief pain inventory, Beck Depression Inventory II, World Health Organization Disability Assessment Schedule (WHODAS 2.0), and a health and demographic questionnaire. Additional data were extracted from the medical record. A raw score of ≥1 on the Subjective Peripheral Neuropathy Screen questions about lower extremity numbness or paresthesia was used to identify peripheral neuropathy. Predictors of disability (as determined by association with World Health Organization Disability Assessment Schedule 2.0 scores) were evaluated bivariately and in a multivariable model. Path modeling was used to identify a parsimonious model to elucidate the mediated effects of peripheral neuropathy on disability. Results: Participants with peripheral neuropathy had more depression symptoms, more pain (severity and interference), and higher disability scores compared with participants without neuropathy. The relationship between neuropathy and disability was mediated by pain interference and depression (standardized root mean residual = .056). Conclusion: In this sample of people with HIV, those with lower extremity peripheral neuropathy reported more severe disability, worse pain, and more depression symptoms than those without neuropathy. The relationship between peripheral neuropathy and disability may be mediated though pain interference and depression. Impact: Distal sensory polyneuropathy is a common comorbidity experienced by people living with HIV and frequently causes pain. This study can help providers direct care toward lessening disability experienced among people with HIV and peripheral neuropathy by targeting interventions for treatment of pain and depression. Lay Summary: People living with HIV may experience disabling painful neuropathy. Treatment for pain and depression may help reduce the disability associated with painful neuropathy.